Electrodeposition and characterization of copper coating on stainless steel substrate from alkaline copper solution containing Ethylenediaminetetraacetate (EDTA) / Nik Norziehana Che Isa...[et al.] - Che Isa, Nik Norziehana; Mohd, Yusairie; Mohd Zaki, Mohammad Hafizudden; Syed Mohamad, Sharifah Aminah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Copper coating was successfully deposited onto 304 stainless steel substrate from pH 8 EDTA solution containing 0.01 M Cu2+ ions, added as CuSO4. The nature of 304 stainless steel electrode reactions in solutions was determined by cyclic voltammetry. Based on cyclic voltammetric analysis, -1.1 V is related to the Cu2+ ions reduction and the suitable applied potential for further electrodeposition process. Chronoamperometric study was done by applying a constant potential at -1.1 V at different deposition times. Morphological observation revealed that deposition time has strongly affected the surface coverage of the copper coating on the 304 stainless steel surface. Crystalline pure copper phase was determined by XRD. The coating has excellent adhesion which passed the tape test. This study showed that the copper coatings with good surface coverage and adhesion can be prepared on the 304 stainless steel substrate.